Lithium intoxication complicated by severe bradycardia after single-incision laparoscopic sleeve gastrectomy: a case report and literature review - Xie, SiJun; Pang, XiaoTian; Yu, ZhengHang; Zhang, ZhongYang; Zhang, Yuan; Ren, YiXing (Frontiers in Surgery, 2026)
BackgroundLithium carbonate has a narrow therapeutic index, and postoperative anatomical/physiological changes after bariatric surgery may markedly alter its pharmacokinetics.CaseA 25-year-old woman with bipolar disorder on long-term lithium therapy developed altered consciousness and profound sinus bradycardia (nadir 27 bpm) approximately 7 weeks after single-incision laparoscopic sleeve gastrectomy. Laboratory testing revealed hyponatremia, acute kidney injury, and a serum lithium level of 4.16 mmol/L.Interventions and outcomesLithium and other psychotropics were discontinued, fluid resuscitation and inotropic support were initiated, and three consecutive sessions of continuous renal replacement therapy (CRRT) were performed. Serum lithium normalized without rebound, Sinus bradycardia recovered, and the patient was discharged without pacemaker implantation. During follow-up, lithium was permanently discontinued and replaced with lamotrigine. Mood remained stable without cardiac or neurologic sequelae.ConclusionPost-bariatric patients receiving lithium should be considered high risk for intoxication. Routine monitoring with early recognition and multidisciplinary collaboration is essential to prevent complications. This case further shows that even extreme lithium-induced bradycardia can be fully reversible with timely withdrawal and extracorporeal clearance, highlighting the need to address reversible causes before permanent pacing.